Manual de consulta en medicina clinica equina - Guzmán Obando, Logans Javier; Orozco Tercero, Walter Walit Jafet; Sáenz García, Arsenio. Asesor; Vanegas Corrales, Deleana. Asesor (Managua (Nicaragua), 2020)
(Es)(En)
Ilus,126 ref., Contiene CD registro CD0125/2021 y con misma clasificación
Monografía (Lic. Med.Vet.)